Automatic quadtree‐based modeling using a coupled SBFEM/SCM approach. Issue 1 (15th March 2018) - Gravenkamp, Hauke; Duczek, Sascha; Birk, Carolin
Abstract: We present an approach for the automatic image‐based modeling in computational mechanics. The geometry is divided into subdomains by employing a quadtree‐decomposition. The scaled boundary finite element method (SBFEM) can directly be applied to quadtree meshes without introducing hanging nodes, while the spectral cell method (SCM) allows for an accurate representation of curved boundaries. Hence, a combination of both methods can lead to highly accurate and reliable results in a fully automatic simulation environment. The performance of this coupled SBFEM/SCM approach is demonstrated by means of a modal analysis of a violin soundboard. (© 2017 Wiley‐VCH Verlag GmbH & Co. KGaA, Weinheim)